OPTIMIZATION OF THE COLLECTING BUSINESS PROCESS FOR EXPRESS DELIVERY SERVICES USING THE BUSINESS PROCESS IMPROVEMENT (BPI) METHOD AT GERAI BERSAMA ASPERINDO MULTIEKSPRES - Susanto, Denies; Inarto, Agoes (Yayasan Education and Social Center, 2025)
In the postal sector, business process efficiency significantly affects customer satisfaction and company performance. Based on observations, several issues were identified in the collecting business process, such as data entry errors, ineffective and inefficient delivery handover processes, and the lack of integration in sales reconciliation, among others. These issues indicate that the collecting business process is not yet optimized. This study aims to optimize the collecting business process at Gerai Bersama Asperindo Multiekspres using the Business Process Improvement (BPI) method. The research method employed is a case study with a qualitative approach. Data collection techniques include document review, interviews, and observations. The data were analyzed using Business Process Management (BPM), outlined through the three phases of Business Process Improvement (BPI): organizing for improvement, understanding the process, and streamlining. In the organizing for improvement phase, Gerai Multiekspres focuses on service efficiency, error reduction, and customer satisfaction through task division, technology utilization, and continuous training. In the understanding the process phase, the collecting process at Gerai Multiekspres involves receiving goods, handover of shipments, and daily sales reconciliation and deposits, comprising a total of 22 activities. The main challenges include the prolonged transaction process, data entry errors, ineffective and inefficient delivery handovers, and manual reconciliation, which slow down operations. Streamlining simplifies the workflow by reducing non-value-adding activities and implementing automation to accelerate operational processes. The results of the study show that the implementation of BPI reduced the process time from 106 minutes to 67 minutes, reduced the number of activities from 22 to 10, and increased throughput efficiency from 71% to 76%.